Experiments and numerical simulations of new biaxially loaded specimens to characterize the behavior of thin metal sheets. Issue 1 (25th October 2016) - Gerke, Steffen; Schmidt, Marco; Brünig, Michael
Abstract: The paper deals with the development of new biaxially loaded specimens to study the damage behavior of ductile metals under different loading conditions. Based on numerical simulations newly designed biaxial specimens are developed and numerically studied while an experimental program has been realized in continuation. The experimental results have been evaluated by digital image correlation (DIC) and compared with the results of finite element simulations. By concideration of different biaxial loading conditions it is possible to cover a wide range of stress triaxialities and Lode parameters in tension, shear and compression domains and consequently the newly proposed specimens facilitate a controlled study of damage and fracture at different stress states. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)